The Temporal Study of Spot and Futures Market Volatility : Cross Linkages among the Equity, Commodity, and Forex Markets in India - Subba, Susmita; Muthu Pandian, B.; Vishal, Ravi Shekhar (Indian Journal of Research in Capital Markets, 2023)
Purpose : The article attempted to generate a volatility series and evaluate its inter & intra relationships across various sub-markets and divisions of the Indian financial market, namely the commodity, equity, and foreign exchange markets. Methodology : The autoregressive conditional heteroskedastic (ARCH) and generalized autoregressive conditional heteroskedastic (GARCH) models were used in the study together with the conventional approach of standard deviation to produce the volatility series. The overall and segment-specific association was analyzed using a correlation matrix. Findings : The analysis revealed a favorable association with the intra-market of the respective markets, although a negative correlation was identified between the equity and commodity spot market and the forex market. Practical Implications : The study aimed to enhance stakeholders’ knowledge of intermediary and inter-market volatility and to investigate the relationship between the Indian financial (equity, commodity, and currency) submarkets. Originality : The study sought to examine the volatility of the Indian market and the interrelationship of volatility among the various submarkets within the Indian financial submarkets using a temporal break based on the incremental movement of every 10,000 points of the BSE sensitivity index (SENSEX).